2017
DOI: 10.1002/cbf.3260
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast differentiation gene expression profiling reveals chemokine CCL4 mediates RANKL‐induced osteoclast migration and invasion via PI3K pathway

Abstract: The migration of osteoclasts (OCs) from circulation and bone marrow into bone surface plays a critical role in the pathogenesis of some bone resorptive diseases, such as rheumatoid arthritis and osteoporosis. To date, how the migration of OCs remains unclear. We investigated gene expression profiling in osteoclastic differentiation of bone marrow-derived macrophages (BMMs) into OCs by microarray analysis. We identified 387 genes overexpressed in osteoclastic differentiation of BMMs. Among them, chemokine CCL4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…56 CCL4 has been found to be an important regulator for osteoclast migration indicating that it is a potential therapy target for bone resorptive diseases. 57 A study reported that CXCL10, CCL5 and CXCL8 chemokines were elevated in the plasma of patients with active RA similar to Th1 associated proinflammatory cytokines TNFα, and IL-6. 58 CXCL10 is primarily secreted by fibroblast-like synoviocytes and infiltrating macrophages in the synovium.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 99%
“…56 CCL4 has been found to be an important regulator for osteoclast migration indicating that it is a potential therapy target for bone resorptive diseases. 57 A study reported that CXCL10, CCL5 and CXCL8 chemokines were elevated in the plasma of patients with active RA similar to Th1 associated proinflammatory cytokines TNFα, and IL-6. 58 CXCL10 is primarily secreted by fibroblast-like synoviocytes and infiltrating macrophages in the synovium.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 99%
“…CX3CL1 derived from OBs enhances osteoclastogenesis by inducing the adhesion of OC precursors to the bone resorption site ( 79 ). A recent study demonstrated that CCL4 is as an important regulator of OC migration via induction of PI3K activation ( 80 ). Furthermore, CCL2 (MIP-1), CCL5 (RANTES), CCL7 (MCP-3), and CXCL12 (SDF-1) can also induce OC migration, resorption activity, adhesion, and survival ( 81 82 ).…”
Section: Osteoclastogenic Cytokines and Chemokinesmentioning
confidence: 99%
“…Disruption of bone homeostasis is caused by increased bone resorption by osteoclasts rather than new bone formation by osteoblasts, and RANKL is a major pro-osteoclastogenic cytokine that mediates osteoclast differentiation ( Park et al., 2017 ; Ono and Nakashima, 2018 ). Thus, the inhibition of osteoclast formation, bone resorption and migration by inhibiting RANKL signaling and downstream pathways is an important target in the treatment of osteoporosis ( Zou et al., 2001 ; Xuan et al., 2017 ). In the present study, we evaluated the mechanism of CTU inhibition of osteoclast differentiation and migration in a RANKL-induced RAW 264.7 and BMM cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, osteoclast migration plays an important role in diseases associated with abnormal bone resorption such as rheumatoid arthritis and osteoporosis. In recent studies, chemokine CCL4 has been shown to mediate cell migration and bone invasion in RANKL-induced bone resorption ( Xuan et al., 2017 ). In this study, CTU downregulated the expression of transcription factors and genes involved in RANKL-induced osteoclast differentiation and migration.…”
Section: Discussionmentioning
confidence: 99%